2014
DOI: 10.5897/ajbr2014.0794
|View full text |Cite
|
Sign up to set email alerts
|

Radiation protection and anti-oxidative effects of garlic, onion and ginger extracts, x-ray exposed albino rats as model for biochemical studies

Abstract: The present study investigates and examines the comparative effects of plant extracts such as, garlic, ginger and onion on some organs (liver, kidney and heart) of x-ray exposed rats, using and assaying some biochemical enzymes. Twenty (20) albino rats with an average weight of (155.00 ± 2.01 g), divided into five groups were used for the study. The rats with exception of the control were exposed to x-ray with ionizing radiation at a dose of 525 kv/s. The results indicate some toxicity conferred on the rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…(HSCs) were proliferated and migrated throughout medullary tissues to expand the number of HSCs and increase hematopoiesis. The entire treatment explained how dietary and metabolic factors could alter the risk of leukemia development following ionizing radiation (Nwachukwu et al 2014). The results of plasma ALT and AST activity indicated that exposure 6Gy radiation significantly (P < 0.05) increased plasma ALT and AST activity relative to control group, while feeding with a diet enhanced with synbiotics reversed the radiation effect (Saad 2012).…”
Section: Discussionmentioning
confidence: 98%
“…(HSCs) were proliferated and migrated throughout medullary tissues to expand the number of HSCs and increase hematopoiesis. The entire treatment explained how dietary and metabolic factors could alter the risk of leukemia development following ionizing radiation (Nwachukwu et al 2014). The results of plasma ALT and AST activity indicated that exposure 6Gy radiation significantly (P < 0.05) increased plasma ALT and AST activity relative to control group, while feeding with a diet enhanced with synbiotics reversed the radiation effect (Saad 2012).…”
Section: Discussionmentioning
confidence: 98%
“…J. Medical Physics, Clinical Engineering and Radiation Oncology [5]. Another study was done on the Antioxidant Effects of Allium cepa and…”
Section: Introductionmentioning
confidence: 99%